A survey of staphylococci isolated in hospital practice - Bradley, J. (1961)
In-patient and out-patient strains of coagulase-positive staphylococci were compared and showed a different phage group distribution. Group III predominated in the in-patient series and accounted for nearly all the antibiotic-resistant strains. The prevalence of phage type 80 in breast abscesses was noted. It was found that one in three coagulase-positive staphylococci isolated from hospital in-patients was sensitive to chloramphenicol and erythromycin only.